THE PROSPECT OF SUSTAINABLE SLUM SETTLEMENT MANAGEMENT IN KAMPUNG BUGIS VILLAGE, TANJUNG PINANG CITY - Aribowo, Kuncoro; Indrayani, Indrayani; Satriawan, Bambang; Khaddafi, Muammar; Wibisono, Chablullah (CV. Radja Publika, 2022)
Handling slum settlements is an issue that continues to be of concern to date as an effort to create a City Without Slums in 2020 and cities and human settlements that are incl usive, safe, resilient and sustainable by 2030 in accordance with the 11th SDG target. Many slum management programs in Indonesia have been implemented but they tend to pay less attention to sustainable aspects. One of the programs carried out by the Government of Indonesia in dealing with slums is the City Without Slum Program (Kotaku). This program is based on community empowerment and is implemented in 20 districts / cities in Indonesia, one of which is in the City of Tanjungpinang, namely Kampung Bugis Village, which is one of the pilot projects for the City Without Slum (Kotaku) Program in 2019.